Leaching Potential of Phosphite Fertilizer in Sandy Soils of the Southern Coastal Plain, USA - Ariel A. Szogi (MDPI AG, 2021)
Novel biotechnology on transgenic plants capable of metabolizing phosphite (Phi), a reduced form of P, could improve the effectiveness of P fertilizers and reduce the P footprint in agriculture with the benefit of suppressing weed growth. However, potassium Phi (K-Phi) salts used as fertilizer are highly soluble in water. At the same time, sandy soils of the Southern Coastal Plain are vulnerable to leaching losses resulting from long-term Pi fertilizer application. We performed a replicated leaching trial using five soil materials that included three surface and two subsurface layers from cultivated topsoil (Ap horizon) with contrasting Phi and Pi sorption capacities. Each soil received three treatments K-Phi at rates 0 (control), 24, and 49 kg P ha−1 and leached twice with de-ionized water. All K-Phi-treated soils leached Phi except for the controls. A phosphorus saturation ratio (PSR) calculated from P, Al, and Fe in acid extracts indicated increasing environmental risk of Phi leaching in soils with lower Phi and Pi sorption capacities at rising rates of applied K-Phi. Because plants rapidly absorb Phi, further studies on the environmental impact of K-Phi fertilizer use should include the interaction of plants with soil properties and soil microbial activity at optimal Phi application rates for growing transgenic plants able to use Phi as a nutrient source.